Analysis of Endo-1,4-?-Glucanase (eglS) Gene in Cellulose-Degrading Bacteria (Bacillus) Based on In Silico Research - Hasanah, Umi Uswatun; Sari, Safitri Anggita Tunjung; Solihah, Jumailatus (Proceeding International Conference on Science and Engineering, 2021)
Abstract. The process of cellulose degradation naturally requires the help of microorganisms. The group of Bacillus bacteria is one of the cellulolytic bacteria that can break down cellulose. The mechanism of cellulose degradation in Bacillus is a complex system and was regulated by a number of genes. One of Bacillus genes that has mechanism of cellulose degradation is eg1S gene. This gene is responsible to hydrolyze the internal glycosidic bonds to reduce the long chain of cellulose. This research examines the comparasion of endo-1,4-?glucanase gene homology in Bacillus that can degrade cellulose. The method of research is in sillico-based research by using National Center for Biotechnology Information (NCBI) website, Clustal Omega website, and MEGA-X software. The results obtained in this research are the identity of endo-1,4-?-glucanase gene, phylogenetic tree, and similarity index in Bacillus that can degrade cellulose. From the research that has been done, it can be concluded that the highest homology ratio of endo-1,4-?-glucanase gene is occupied by Bacillus subtilis strain AuChE413 and Bacillus subtilis strain IARI-SP-1 with 100% identical similarities.